2016
DOI: 10.1080/07347332.2016.1225145
|View full text |Cite
|
Sign up to set email alerts
|

Personality and psychological distress among older adult, long-term cancer survivors

Abstract: This research examines a model of how personality (Five-Factor Model) is related to adjustment to cancer in later life in terms of the presence of continuing cancer-related worry and depression among older adult, long-term cancer survivors. Data from an NCI-funded study with 275 older adult (age 60+), long-term (5+ years) survivors of breast, prostate, and colorectal cancer were examined. Regression analyses identified neuroticism as the strongest predictor of cancer-related worry along with continuing cancer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 32 publications
3
28
2
3
Order By: Relevance
“…The latest scienti c reports show that some personality traits have an impact on the risk of depression occurrence in chronically ill patients. However, results of the quoted research are not consistent in respect of speci c personality traits as indicators of depression [21][22][23]. Similarly, our work did not con rm a signi cant correlation between the examined personality traits and intensity of depression.…”
Section: Discussioncontrasting
confidence: 91%
“…The latest scienti c reports show that some personality traits have an impact on the risk of depression occurrence in chronically ill patients. However, results of the quoted research are not consistent in respect of speci c personality traits as indicators of depression [21][22][23]. Similarly, our work did not con rm a signi cant correlation between the examined personality traits and intensity of depression.…”
Section: Discussioncontrasting
confidence: 91%
“…Other studies identified neuroticism as the strongest predictor of cancer-related worry along with continuing cancer-related symptoms. For depression, three personality dimensions (neuroticism, conscientiousness, and agreeableness) were significant predictors [22]. Rachel et al examined associations between illness representation dimensions specified by the self-regulation model, coping and mood in 61 recently diagnosed gynaecological cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research has delved into associations between MAC and personality traits . Moreover, the majority of the studies identified focused on long‐term cancer survivors …”
Section: Introductionmentioning
confidence: 99%